Pelatihan Teknik Pemeriksaan Lembar Jawaban pada Soal Pilihan Ganda Berbasis Android pada Guru MGMP Biologi - Astija Astija; Andi Tanra Tellu; Musdalifah Nurdin; Syech Zainal (Jurnal Kreatif Online, 2021)
The purpose of this study was to describe the improvement of the ability of Biology Subject Teachers' Deliberation teachers through training in the technique of examining answer sheets on android-based multiple choice questions. The research subjects were 16 people. The method used is descriptive research. Data were analyzed descriptively. The activity was carried out by presenting the material, then installing the application program, the practice of using smartphones and their applications on the student answer sheets being tested, reading and interpreting the analysis results from the examination of the application program, reporting the examination results and sending the examination results from the application program. This activity is planned to be carried out programmatically with a training model that integrates theory and practice. The results of the research on increasing the ability of Biology Subject Teachers' Deliberations through training in the technique of examining answer sheets on android-based multiple choice questions in the criteria of being able to be 63% based on the aspects measured.